Assessment of seasonal trophic state of tropical man-made lake, The Cirata Reservoir. (May 2019) - Ariyani, M; Agustian, M; Maharani, G S; Sunardi,
Abstract: Evaluation of 4-year data set (2013-2016) to define the trophic state of Cirata Reservoir among the seasons and its impact on the reservoir sustainability has been performed. Cirata is one of the cascade reservoirs located on the Citarum River, with the main purpose for electricity generation through a hydropower plant. Data were obtained from eleven sampling stations of monitoring programs in the Cirata Reservoir. The technique for water sample collection and analysis referred to SNI (Indonesian National Standard) 03-7016-2004 and standard method focussing on phosphate, Chlorophyll- a and transparency. This study indicated that the trophic condition of Cirata Reservoir, as a tropical man-made, was unique and dynamic compared to lakes in the temperate season. The results showed that the reservoir water in the last four years was already eutrophic whether in rainy, intermediate or dry seasons with Trophic State Index were 60.42; 59.00 and 57.32 respectively. This study showed that the inlet and centre area of the reservoir had a higher trophic index than the outlet area. This phenomenon indicated that the main sources of eutrophication in Cirata Reservoir came from both the catchment area of the reservoir (i.e. upper Citarum) and on-site the reservoir. Phosphate has been established as the nutrient that commonly limits the productivity in Cirata reservoir. Thereby, phosphate control is critical for the eutrophication mitigation in Cirata. To cope with this condition, strategies must be applied whether to control the phosphate utilization in the catchment or inside the reservoir area.